Efektivitas Program Rumah Anak Prestasi Berkebutuhan Khusus (Rapbk) Sebagai Strategi Upaya Pengurangan Kemiskinan Di Kota Surabaya - Holifah, Nur; Ikmal, Novita Maulida; Iswanto, Denny (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
Poverty remains a complex social problem in urban areas, especially for families with children with special needs (ABK). This condition not only causes economic limitations, but also limited social and educational access. The Surabaya City Government, through the Social Services Agency, launched the Rumah Anak Prestasi Berkebutuhan Khusus (Special Needs Children's Home) Program as a form of social empowerment for families with children with special needs, with a focus on skills development, economic improvement, and social inclusion. This study aims to analyze the effectiveness of the program as a poverty reduction strategy in Surabaya using the theory of program effectiveness according to Budiani (2007), which includes four indicators: program targeting accuracy, program socialization, program goal achievement, and program monitoring. This study uses a descriptive qualitative approach, with the location at the Rumah Anak Prestasi Berkebutuhan Khusus (Special Needs Children's Home) operating under the Surabaya City Social Services Agency in 2025. The results of the study indicate that this program is substantively effective in increasing family economic capacity through skills training such as painting, sewing, screen printing, and batik. Sales of crafts made by children with special needs contribute to increased family income and strengthen children's self-confidence. However, the program's effectiveness still needs to be improved in terms of monitoring and economic sustainability after participants graduate from the training. This study concludes that the Home for Achieving Children with Special Needs Program is an innovative strategy by the Surabaya city government to reduce poverty based on social inclusion and empowerment of families with special needs.